A walking intervention to reduce inflammation in patients with diabetes and peripheral arterial/artery disease: A pilot study - Collins, Tracie C (SAGE Open Med, 2013)
OBJECTIVES: In this pilot study, we sought to determine whether walking reduces inflammation in patients with diabetes mellitus and peripheral arterial/artery disease. METHODS: We obtained blood samples from patients with diabetes mellitus and peripheral arterial/artery disease. Intervention participants were advised to walk for 50 min 3 days per week for 6 months. Participants completed assessments of comorbidities and walking ability. Difference-in-difference analyses were used to assess the relationship between group assignment and each biomarker over time. RESULTS: We randomized 55 participants (control = 25 and intervention = 30). At 6 months and based on p values of <0.20, vascular cellular adhesion molecule, beta-2 microglobulin, total cholesterol, and triglycerides demonstrated a greater decrease among participants randomized to the intervention compared to the control. CONCLUSIONS: Walking may reduce inflammation in persons with diabetes mellitus and peripheral arterial/artery disease. Further research is needed to determine the impact of walking on inflammation in persons with vascular disease.